2008
DOI: 10.1007/s10681-008-9739-9
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and field performance of transgenic Korean Bt rice lines resistant to rice yellow stem borer

Abstract: Transgenic Korean rice plants containing the cry1Ab gene were developed for resistance against yellow stem borer (Scirpophaga incertulas, YSB). More than 100 independent transgenic lines from three Korean varieties (P-I, P-II and P-III) were generated. The amount of Cry1Ab in transgenic T 0 plants was as high as 2.88% of total soluble proteins. These levels were suYcient to cause 100% mortality of YSB larvae. The majority of T 1 transgenic lines originated from the varieties P-I and P-II followed a Mendelian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 45 publications
1
36
1
1
Order By: Relevance
“…Previous evaluation of the same Bt GE rice lines did not show any yield losses caused by the underlying fitness cost under different experimental designs (Huang et al 2008;Wang et al 2010). The above findings are not in accordance with reports from other studies in which some insect-resistant Bt GE rice lines showed various degrees of yield loss when ambient insect pressure was extremely low (Chen et al 2006;Kim et al 2008;Xia et al 2010), probably reflecting the underlying cost of the transgene(s). The discrepancy between these results clearly demonstrates a case-specific situation concerning the benefit and cost of different transgenes and transgenic events that influence the performances of GE crops.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Previous evaluation of the same Bt GE rice lines did not show any yield losses caused by the underlying fitness cost under different experimental designs (Huang et al 2008;Wang et al 2010). The above findings are not in accordance with reports from other studies in which some insect-resistant Bt GE rice lines showed various degrees of yield loss when ambient insect pressure was extremely low (Chen et al 2006;Kim et al 2008;Xia et al 2010), probably reflecting the underlying cost of the transgene(s). The discrepancy between these results clearly demonstrates a case-specific situation concerning the benefit and cost of different transgenes and transgenic events that influence the performances of GE crops.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies have indicated that many insect-resistant GE rice lines can have significant yield benefits under insect attacks (Tu et al 2000;Chen et al 2006;Huang et al 2008;Wang et al 2010), in addition to their positive impacts on agricultural ecosystems and more environmentally friendly farming practices (Huang et al 2005(Huang et al , 2008. However, studies have also indicated the underlying fitness cost of some insect-resistant GE rice lines under insect-free or low-insect environmental conditions (Chen et al 2006;Kim et al 2008;Xia et al 2010), which might potentially lead to some degree of yield loss when ambient insect pests are scarce. In addition, it is also important to detect effects on yield of an insect-resistant GE crop caused by target and non-target insects in a well-designed field experiment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic sugarcane plants were shown to produce sorbitol, gentiobiose and gentiobiitol (Chong et al 2007(Chong et al , 2010, and to confer resistance to herbicides or pest (Enríquez et al 2000;Weng et al 2006). Genetic transformation using insecticidal Bt genes is regarded as an effective method to develop insect-resistant transgenic plants (Kim et al 2008;Valderrama et al 2007). Since 1990s, several methods for generation of transgenic sugarcane plant have been established, such as microprojectile bombardment and electroporation of embryogenic cells (Arencibia et al 1995;Bower and Birch 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Bashir et al (2004) noticed significant reduction in plant height of the transgenic rice lines L-5, L-13, and L-6-411 compared to the controls. Kim et al (2008) also observed highly significant reduction in plant height in insect-resistant transgenic lines of three Korean rice varieties. Three lines (S-1-02, S-2-04, and S-5-01) showed a significant increase in the number of fertile tillers compared to the controls while no significant increase or decrease in the number of fertile tillers per plant was observed in the other three lines.…”
Section: Field Performance Of Transgenic Linesmentioning
confidence: 76%
“…However, a few studies indicated that transgenic lines exhibited lower grain yields compared to their respective controls (Kim et al, 2008). These variations in phenotypic and agronomic characters may be a result of somaclonal variations, insertion mutagenesis, or transgene-induced endogenous gene silencing (Larkin and Scowcroft, 1981;Matzke et al, 1993;Kathuria et al, 2007).…”
Section: Field Performance Of Transgenic Linesmentioning
confidence: 99%